Thermal induced yellowing of peroxide bleached birch pulp - Nygren, Alexander (Luleå tekniska universitet, Industriell miljö- och processteknik, 2020)
Brightness reversion, also known as yellowing, is a well-known phenomenon which means that the brightness of paper products decreases during ageing. The name of this phenomenon is based on that paper products usually change in color towards yellow during ageing. Yellowing is considered to occur due to a mixture of chemical and physical factors, which makes it a complex problem for the pulp & paper industry. The majority of the literature and research conducted with respect towards yellowing claims that light and heat is the two main factors that contributes the most to a brightness reversion, depending on the type of pulp and process that is utilized. Smurfit Kappa in Piteå is a manufacturer of the paper grade Kraftliner and has during some occasions noted unstable brightness. Based on previous work at Smurfit Kappa, it is known that the finished liners produced from bleached pulp in a completely chlorine-free process is very sensitive to heat, especially for longer periods of time during storage. It has also been documented that the storage temperature for paper products is of great importance, especially the cooling rate of the paper-rolls from production, which could take around two weeks to reach the ambient temperature. This thesis work, alongside with a literature study as a basis will examining the effect of pH towards yellowing during thermal exposure. Through a factorial experiment it was initially found that the yellowing is favored by higher temperatures in conjunction with lower pH values. In order to obtain a brightness reversion of a paper product within a reasonable timeframe an accelerated aging method was used according to the ISO standard 5630-1. Throughout this thesis is the brightness reversion expressed in the so-called b* value, which indicates the color change from blue to yellow. Further experiments, including ageing methods with moisture, also concluded that an acidic pH results in a more severe yellowing. It was also observed that the pH was decreasing during experiments of pulp ...